Pembuatan Biobriket Kulit Kakao dan Sekam Padi dengan Perekat Gondorukem yang dilarutkan dengan Ethanol - Muhammad Nabil Zhillan Abdillah; Rivaldi Aristio; Isni Utami (Jurnal Serambi Engineering, 2024)
Biomass is a solid waste that can be used as a fuel source. One attempt to provide alternative energy is to use organic waste as a feedstock. Biomass conversion can increase the calories per unit volume, is easy to transport and has the same size. Cocoa shells and rice husks can be processed into bricks that can be used as fuel for households and small industries. The study aims to find out the composition of briquette from cocoa shells and rice husks mixture that meets the Indonesian National Standard. The parameters are proximate and caloric test. The variations are the comparison of the composition of cocoa shells and rice husks (30:10; 25:15; 20:20; 15:25; 10:30g) and the variation of the adhesive gondorukem composition (5%; 10%; 15%; 20%; 25%). The results show that the best conditions are on the briquette variable 20 : 20 (cocoa shells : rice husks) with adhesives 15% with a caloric value of 5232,91 cal/gr; water content 7,8%; ash content 7,6%; flying substance 6,1%; and fixed carbon 78,054%. Based on the test results of the variable briket 20:20 with the 15% glue, it complies with SNI 01-6235-2000.